“You have not advertised out of it”: Samuel Taylor Coleridge and Francis Jeffrey on Authorship, Networks and Personalities - Sangster, Matthew (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2012)
This essay begins by establishing the vexed status of authorship in the early nineteenth century, a period during which the professional author and the writer-as-artist remained conflicted and nascent ideas but in which the authority mustered by judicious quarterly critics was both potent and profitable. It considers the challenges and possibilities of this situation by closely examining an 1808 correspondence between Samuel Taylor Coleridge and Francis Jeffrey, editor of the Edinburgh Review. These letters, addressing Coleridge’s reputation and the propriety of reviewing the anti-slavery campaigner Thomas Clarkson, are deeply revealing both as to Coleridge’s ambivalent feelings about the effectiveness of his own self-presentations and regarding the strongly socialised positions that successful authors tended to occupy. I pay particular attention to the distinctions Coleridge draws between Wordsworth, inured to passing periodical criticism and destined for an eventual triumph, and Clarkson, who Coleridge “cannot regard as a mere author” and whose work he “cannot read or criticise [...] as a mere literary production” (CL 3: 119). While Coleridge privileges Clarkson’s socially-created self, he also claims a space for a more devoted kind of authorship, attempting to persuade a sceptical Jeffrey that he can redefine himself and potentially effect great changes through writing. Coleridge’s obvious concern with the ways that Jeffrey sees him and the pragmatic requests he makes reveal him to be cannily engaged in the business of manipulating social reputations; while the letters are early symptoms of an eventual shift in how authorship was conceived, they also reveal Coleridge’s investment in older, less textually-focused forms of influence.